On Weakly Singular Versions of Discrete Nonlinear Inequalities and Applications - Kelong Cheng; Chunxiang Guo; Qingke Zeng (Abstract and Applied Analysis)
Some new weakly singular versions of discrete nonlinear inequalities are established, which generalize some existing weakly singular inequalities and can be used in the analysis of nonlinear Volterra type difference equations with weakly singular kernels. A few applications to the upper bound and the uniqueness of solutions of nonlinear difference equations are also involved.